Role of Local Flow Conditions in River Biofilm Colonization and Early Growth. (26th March 2014) - Coundoul, F.; Bonometti, T.; Graba, M.; Sauvage, S.; Sanchez Pérez, J.‐M.; Moulin, F. Y.
Abstract Direct numerical simulations of a turbulent boundary layer flow over a bed of hemispheres of height h are performed using an immersed boundary method for comparison with river biofilm growth experiments performed in a hydraulic flume. Flow statistics above the substrates are shown to be in agreement with measurements performed by laser Doppler velocimetry and particle image velocimetry in the experiments. Numerical simulations give access to flow components inside the roughness sublayer, and biofilm colonization patterns found in the experiments are shown to be associated with low shear stress regions on the hemisphere surface. Two bed configurations, namely staggered and aligned configurations, lead to different colonization patterns because of differences in the local flow topology. Dependence with the Reynolds number of the biofilm distribution and accrual 7 days after inoculum is shown to be associated to local flow topology change and shear stress intensity. In particular, the shear stress τ on the surface of the hemispheres is found to scale as <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj8n1ns35" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μu*/hRet0.26</alternatives>, where Ret = u*h/ν, with u* as the log law friction velocity and ν as the fluid kinematic viscosity. This scaling is due to the development of boundary layers along the hemisphere surface. Associated with a critical shear stress for colonization and early growth, it explains the increasing delay in biomass accrual for increasing flow velocities in the experiments. Copyright © 2014 John Wiley & Sons, Ltd.